Review of Hierarchy-of-Effects (Hoe) models and higher education advertising in Malaysia - Yaakop, Azizul Yadi; Mahadi, Nomahaza; Ariffin, Zailin Zainal; Omar, Siti Sarah (Academic Research Publishing Group, 2018)
The most enduring and controversial models of advertising effectiveness are the Hierarchy-of-effects (HOE) models, which are of particular interest to researchers in marketing and advertising. This paper gives emphasis on the selection of these hierarchical models in the context of Higher Education Institutions (HEIs) in Malaysia. The notion of raising awareness and interest, followed by desire and action is very seductive in its simplicity, and provides a clear focus for Higher Education advertising. In light of the criticisms of these models, this conceptual paper compares and contrasts the more important advertising models and reflects on the relevance of these simple models in relations to the advertising focus in HEIs.The authors conclude that HOE models fail to adequately represent the impact of the advertising process on the complex emotional/rational decision-making that takes place when choosing HEIs. Advertising‟s impact on the choice process is far more complex: developing brand desire through brand image is an important purpose of advertising. The authors are also in agreement with the notion of an essential understanding of other marketing areas such as brand identity, meaning and reputation of higher education institutions through a variety of qualitative and quantitative methods to communicate effectively with the stakeholders.